SEGREGASI GENDER DALAM PEMBELAJARAN ILMU FALAK DI PESANTREN SALAFIYAH LIRBOYO KEDIRI DAN PESANTREN MODERN ASSALAM SURAKARTA SEBAGAI UPAYA PEMBERDAYAAN PERAN PEREMPUAN - Nihayatur Rohmah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2017)
Gender mainstreaming in educational institutions is the policy implementation. Based on National Education Minister Regulation No. 84 of 2008 on Guidelines for Mainstreaming Gender Education, then on its appropriateness in all formal educational institutions is mandatory, including a boarding school. Gender equality and justice requires that men and women have access to (opportunities) and equal participation in the educational process, to have a balanced control or authority over resources, and benefit equitably educational outcomes. The study was conducted at boarding Lirboyo and Pesantren Assalam. object of research is the study astronomy. The method applied in this study include (1) Approach and type of study: This study was conducted with a qualitative descriptive approach, this approach was used to explore the process of implementation of gender-based segregation class and excellence as well as the problems that occur in it. (2) Data collection: Observation Techniques, Interview Techniques, and Technical Documentation. (3) Data Analysis Techniques: To analyze the qualitative data analysis techniques the author uses descriptive. The results of this study indicate that the real separation of classes between women and men by applying segregation horizontal which is optional to have positive effects in the learning process, but if the separation is done because of the gender gap by applying segregation vertically, then the model led to negative effects for learners. Achievement and Role of the learner directly proportional to access (opportunities) given. Policy education institutions should be redesigned and directed to responsive and gender-neutral benefit-oriented. Thus, the separation of this class can be applied in schools to improve student achievement